A STUDY TO ASSESS THE CONTRAST SENSITIVITY OF THE HUMAN VISUAL SYSTEM IN PATIENTS WITH OR WITHOUT DIABETES IN A TERTIARY CARE HOSPITAL - RAJGADIA, NIKITA; BHASKARAN, BINDU; DIVYA, N.; VEERAMANI, V. PANIMALAR A.; IKRAM, SYEDA SADIYA (International Journal of Current Pharmaceutical Research, 2020)
Objective: The objective of our study was to assess the variations in contrast sensitivity values of normoglycemic subjects and that of type II diabetic subjects of the same age group. It was also aimed at finding the visual acuities and study the associations of it with contrast sensitivity if any. Methods: It was a hospital-based comparative cross-sectional descriptive study conducted in the out-patient department of the Department of Ophthalmology, Saveetha Medical College, Hospital, Chennai. Visual Acuity and Contrast Sensitivity of 50 Type II Diabetic individuals and 50 age-equivalent control group subjects were measured using the Snellen’s chart and Pelli-Robson chart, respectively, during the months of January to March 2020. Results: Contrast Sensitivity measurements from 50 subjects with Non-Insulin dependent Diabetes Mellitus (NIDDM) were obtained. The subjects were the ones who had minimal or no diabetic retinopathy. It was observed that there is a significant association between reduced contrast sensitivity and Diabetes (P value<.00008). We also noted that CS may be reduced without corresponding loss of Visual Acuity. Hence, both visual acuity and contrast sensitivity measurements are helpful in the assessment of visual impairment due to diabetic eye disease. Conclusion: The contrast sensitivity can be seen as an early marker for visual impairment in diabetic eye care.